Elevated levels of the methyltransferase SETD2 causes transcription and alternative splicing changes resulting in oncogenic phenotypes - Bhattacharya, Saikat; Reddy, Divya; Zhang, Ning; Li, Hua; Workman, Jerry L. (Frontiers in Cell and Developmental Biology, 2022)
The methyltransferase SETD2 regulates cryptic transcription, alternative splicing, and the DNA damage response. It is mutated in a variety of cancers and is believed to be a tumor suppressor. Counterintuitively, despite its important role, SETD2 is robustly degraded by the proteasome keeping its levels low. Here we show that SETD2 accumulation results in a non-canonical deposition of the functionally important H3K36me3 histone mark, which includes its reduced enrichment over gene bodies and exons. This perturbed epigenetic landscape is associated with widespread changes in transcription and alternative splicing. Strikingly, contrary to its role as a tumor suppressor, excessive SETD2 results in the upregulation of cell cycle-associated pathways. This is also reflected in phenotypes of increased cell proliferation and migration. Thus, the regulation of SETD2 levels through its proteolysis is important to maintain its appropriate function, which in turn regulates the fidelity of transcription and splicing-related processes.